A 71-year-old Woman with CREST Syndrome and Multiple Waxy Facial Papules and Plaques: A Quiz - Nidia Planella-Fontanillas; David Pesqué; Laura Parra-Navarro; Ramon M. Pujol (Medical Journals Sweden, 2024)
Abstract is missing (Quiz)